Game-Based Learning Application in Chemistry Learning: A Systematic Literature Review - Sukirno Putri, Isma Yanti Vitarisma; Rahayu, Sri; Dasna, I Wayan (Jurnal Pendidikan MIPA, 2022)
Game-based learning attention to the design of learning and game that can help the learning process be fun, creative, innovative, and not boring. This research aimed to review empirical research articles in chemistry learning using the Systematic Literature Review (SLR) method is to identify, analyze, and interpret the findings on the research topic published from 2017 to 2021. Twelve articles were identified through a search engine providing international and national journal pages that could be accessed using ERIC and Scopus databases. The articles studied in terms of objectives, learning design, and game implementation in learning. The results review focuses on increasing knowledge, understanding concepts, learning outcomes, critical thinking, motivation, emotions, literacy, and student independence. Using digital games is more widely applied in chemistry learning because of interest in educational technology having a better evaluation of the subject matter studied and the achievement of a deeper understanding.Keywords: game-based learning, chemistry learning, literature review.DOI: http://dx.doi.org/10.23960/jpmipa/v23i1.pp01-12